Lineage-tracing cells born in different domains along the PD axis of the developing Drosophila leg. - Weigmann, K.; Cohen, S.M. (Development, 1999)
Patterning of the developing limbs by the secreted signaling proteins Wingless, Hedgehog and Dpp takes place while the imaginal discs are growing rapidly. Cells born in regions of high ligand concentration may be displaced through growth to regions of lower ligand concentration. We have used a novel lineage-tagging method to address the reversibility of cell fate specification by morphogen gradients. We find that responses to Hedgehog and Dpp in the wing disc are readily reversible. In the leg, we find that cells readily adopt more distal fates, but do not normally shift from distal to proximal fate. However, they can do so if given a growth advantage. These results indicate that cell fate specification by morphogen gradients remains largely reversible while the imaginal discs grow. In other systems, where growth and patterning are uncoupled, nonreversible specification events or 'ratchet' effects may be of functional significance.